2010
DOI: 10.1002/pssa.201026242
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐transition studies of Ba0.90Ca0.10(Ti1−xZrx)O3 ferroelectric ceramic compounds

Abstract: Phone: þ55 16 3373 9828, Fax: þ55 16 3373 9824Perovskite-structured Ba 0.90 Ca 0.10 (Ti 1Àx Zr x )O 3 ceramics were prepared in this work and subsequently studied in terms of composition-dependent dielectric and high-resolution longrange order structural properties from 30 to 450 K. The dielectric response of these materials was measured at several frequencies in the range from 1 kHz to 1 MHz. Combining both techniques, including Rietveld refinement of the X-ray diffraction data, allowed observing that, when i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…The decrease in the intensity of the FT peaks can be interpreted in terms of either a decrease in the number of Ba neighbors or an increase in the Debye-Waller factor value. According to previous XRD studies [30], these samples exhibit a cubic symmetry at room temperature. Therefore, at least for the Ba-O first coordination shell, no variation in the number of neighbors is expected.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…The decrease in the intensity of the FT peaks can be interpreted in terms of either a decrease in the number of Ba neighbors or an increase in the Debye-Waller factor value. According to previous XRD studies [30], these samples exhibit a cubic symmetry at room temperature. Therefore, at least for the Ba-O first coordination shell, no variation in the number of neighbors is expected.…”
Section: Resultsmentioning
confidence: 60%
“…Ba 0,9 Ca 0,1 Ti 1Àx Zr x O 3 ceramic samples, hereafter labeled BCZT100 * x (where x = 0.00, 0.05, 0.09, 0.18, 0.20, 0.22, 0.24 and 0.27), were prepared by the solid-state reaction method. A detailed description of the sample preparation can be found elsewhere [30].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the Curie temperature (T C ) obviously shifts to room temperature. 11,12 Wang et al reported that when substituting Ca 2+ for Ba 2+ at the A-site in BT ceramics, T R-O and T O-T decrease. At the same time, T C does not obviously change owing to the enhancement of atomic polarizability and the shrinkage of the unit cell volume having opposing effects.…”
Section: Introductionmentioning
confidence: 99%
“…In lead-and barium-based perovskite ferroelectric relaxor materials, above and below the temperature of maximum of dielectric permittivity (T m ), the X-ray diffraction (XRD) technique shows the existence of a long-range order cubic symmetry with no phase transition [11,12]. However, the observation of a cubic symmetry is not compatible with the observation of a relaxor state in these samples.…”
Section: Introductionmentioning
confidence: 99%